Postural hypotension associated with inappropriate choice of drug treatment of benign prostatic hyperplasia (2015)
A case of a 76 year old Colombian patient who developed an episode of postural hypotension, after using 4mg of doxazosin for treatment of benign prostatic hypertrophy (BPH) is presented. Because of his age and severity of symptoms (asthenia, weakness, adynamia), the patient was hospitalized. Changing doxazosin by tamsulosin allowed control of symptoms of BPH with no further episodes of orthostatic hypotension.